Design and integration of a solar photovoltaic system for mechanized and sustainable cocoa pod splitting - Frederick Abangba Akendola; Clement Adekunle Komolafe; Eric Ofori-Ntow Jnr; Richard Opoku; George Yaw Obeng (Solar Compass)
Cocoa production is crucial to advancing economies. Conventional manual cocoa pod splitting is inefficient, labor-intensive, and hazardous, but mechanical cocoa pod splitting is underutilized due to unreliable energy sources. This research designs and integrates a solar photovoltaic (PV) system to power a cocoa pod-splitting machine for addressing the critical challenge of access to sustainable energy and postharvest handling technology in off-grid cocoa-growing communities. The design adopted an energy demand analysis, environmental assessment, system simulation and practical design implementation to validate the theoretical model and ensure enhanced operational efficiency, sustainability and reliability. An independent PV system consisting of five 275 W monocrystalline panels, 24 V, 40 A charge controller, 24 V hybrid GEL battery bank, and 1.3 hp DC motor was designed based on energy demand, theoretically modeled in MATLAB/Simulink and tested under real solar conditions in Ghana. The system demonstrated consistent energy supply to the machine, with sufficient autonomy for three operating days, whilst producing 5843.75 Wh/day, which surpasses the 4720.46 Wh/day energy requirement of the machine by 23.7%. Real-world performance aligned closely with simulation predictions, confirming the PV system’s viability, scalability and reliability. Analysis of variance conducted at a significance level of 0.05 to test for the statistical significance of differences in mean voltage supply across varying irradiance levels obtained an F−statistic=1.301<F−critical=3.354, and a P−value=0.289>α=0.05, demonstrating the solar PV reliability in operational voltage under varying solar conditions. The outcome of the experiment indicated a splitting efficiency of 98.92 %, a separation efficiency of 91–96.5 % and a bean damage proportion of 1.03 % with a 60 cocoa pods/minute throughput. The study achieves up to 74% improvement while maintaining accessible, eco-friendly and sustainable energy independence relative to prior systems. In conclusion, a solar PV system was successfully developed and implemented to power a cocoa pod-splitting machine, which supplied sufficient, sustainable, reliable and eco-friendly energy to address energy challenges in off-grid cocoa farming communities. Tests showed that the performance of the solar-powered cocoa pod splitting machine was robust, demonstrating a significant improvement over previous systems. The integration of renewable energy improves sustainability, minimizes reliance on fossil fuel and contributes to achieving SDG 7, 9, and 13 in postharvest agricultural mechanization.